A Anchoring Technique Using Long Bent Rods for Open Reduction of Thoracolumbar Dislocation. Issue 9 (November 2021) - Guo, Xiaohui; Wang, Baocang; An, Yi; Jin, Xin; Guo, Zhiliang; Han, Shuo; Huo, Yongxin; Liu, Lanze
Abstract : Objective: The purpose of this study was to evaluate the effectiveness of a novel surgical open reduction method for thoracolumbar dislocation. Materials and Methods: This study included a total of 15 patients of thoracolumbar dislocation. All patients underwent posterior thoracolumbar open reduction and fixation using this technique. Preoperative x-ray, computed tomography (CT), and magnetic resonance imaging were used to evaluate the dislocation. The American Spinal Injury Association grade of spinal cord injury before and afer the operation were record. All patients were followed up for 2 years, and x-ray, CT were used to observe postoperative reduction and fusion. Results: Postoperative x-ray and CT images of all patients indicated good recovery of the spinal sequence, and no neurological deterioration or surgically related complications occurred. All patients were followed up for 2 years, no patients were lost to follow-up. During the follow-up period, x-ray and CT images showed no complications related to internal fixation such as fracture and loosening of screws and rods were found. Conclusion: A anchoring technique using long bent rods is a safe, simple, accurate, and easy to replicate and implement method, which can be applied in the surgical treatment for thoracolumbar dislocation.